Growth of multiorientated polycrystalline MoS2 using plasma-enhanced chemical vapor deposition for efficient hydrogen evolution reactions - Na Liu (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Molybdenum disulfide (MoS2) has attracted considerable attention as a promising electrocatalyst for the hydrogen evolution reaction (HER). However, the catalytic HER performance of MoS2 is significantly limited by the few active sites and low electrical conductivity. In this study, the growth of multiorientated polycrystalline MoS2 using plasma-enhanced chemical vapor deposition (PECVD) for the HER is achieved. The MoS2 is synthesized by sulfurizing a sputtered pillar-shaped Mo film. The relatively low growth temperature during the PECVD process results in multiorientated MoS2 with an expanded interlayer spacing of ~0.75 nm, which provides abundant active sites, a reduced Gibbs free energy of H adsorption, and enhanced intralayer conductivity. In HER applications, the PECVD-grown MoS2 exhibits an overpotential value of 0.45 V, a Tafel slope of 76 mV dec−1, and excellent stability in strong acidic media for 10 h. The high HER performance achieved in this study indicates that two-dimensional MoS2 has potential as an electrocatalyst for next-generation energy technologies.